Analisis Perubahan Mata Pencaharian Nelayan Suku Bajo di Desa Tapulaga Kecamatan Soropia Kabupaten Konawe - Filma, Nur; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness, Halu Oleo University, 2018)
This study aims to know the impact of the transition of livelihood of Bajo fishermen on the economic condition of fishermen community in Tapulaga Village Konawe District. This research was conducted in March until April 2018. The sample determination was done by census by taking all the respondents who numbered 8 fishermen who switch their livelihood. The data obtained from the research results are tabulated according to the variables observed and presented in quantitative descriptive. The result of the research shows the impact of the shifting livelihood of Bajo fishermen to the economic condition of the community in Tapulaga Village increased after the transition of livelihood in terms of income level, expenditure level, housing level, and asset ownership